The natural history of epithelioid sarcoma. A retrospective multicentre case-series within the Italian Sarcoma Group. Issue 7 (July 2020) - Frezza, Anna Maria; Sbaraglia, Marta; Lo Vullo, Salvatore; Baldi, Giacomo Giulio; Simeone, Noemi; Frenos, Filippo; Campanacci, Domenico; Stacchiotti, Silvia; Pasquali, Sandro; Callegaro, Dario; Gambarotti, Marco; Barisella, Marta; et al.
Abstract: Introduction: This case-series is aimed to describe the natural history of epithelioid sarcoma (ES) and to provide insights into the differential clinical behaviour of its two variants ("classic-type" and "proximal-type"). The value of a subtype-adapted grading system based on pathological features is explored. Methods: Data from consecutive, primary, localised, INI1-deleted ES operated at three Italian sarcoma reference centres (1995–2015) were included. Centralised pathological review was performed. Classic-type ES was broken down into "high-grade" and "low-grade", according to number of mitoses, evidence of necrosis and nuclear atypia. Five- and 10-year overall survival (OS) and crude cumulative incidence (CCI) of local recurrence (LR) and distant metastasis (DM) were estimated. Results: Fifty-two patients were included. 5- and 10-year OS estimates were 70% and 47% in the whole series, 57% and 37% in patients with proximal-type ES, 77% and 54% in patients with classic-type ES (P = 0.02). In classic-type ES, 5- and 10-year OS was higher for low-grade (95% and 72%, respectively) than high-grade tumours (P = 0.002). 5- and 10-year CCI estimates for LR were 21% and 33% in the whole series. 5- and 10-year CCI estimates for DM were 35% and 39% in the whole series, both 28% in classic-type ES, 47% and 59% in proximal-type ES (P = 0.03). Conclusions: Suffering from a proximal- or a classic-type is the stronger predictor of outcome in patients with localised ES, with proximal-type ES patients having lower survival due to a higher tendency toward metastatic spreading. However, the "high-grade" classic-type ES was associated with outcomes close to proximal-type ES.